Gut dysbiosis induced by cardiac pressure overload enhances adverse cardiac remodeling in a T cell-dependent manner. Issue 1 (9th November 2020) - Carrillo-Salinas, Francisco J; Anastasiou, Marina; Ngwenyama, Njabulo; Kaur, Kuljeet; Tai, Albert; Smolgovsky, Sasha A.; Jetton, David; Aronovitz, Mark; Alcaide, Pilar
ABSTRACT: Despite the existing association of gut dysbiosis and T cell inflammation in heart failure (HF), whether and how gut microbes contribute to T cell immune responses, cardiac fibrosis and dysfunction in HF remains largely unexplored. Our objective was to investigate whether gut dysbiosis is induced by cardiac pressure overload, and its effect in T cell activation, adverse cardiac remodeling, and cardiac dysfunction. We used 16S rRNA sequencing of fecal samples and discovered that cardiac pressure overload-induced by transverse aortic constriction (TAC) results in gut dysbiosis, characterized by a reduction of tryptophan and short-chain fatty acids producing bacteria in WT mice, but not in T cell-deficient mice ( Tcra −/- ) mice. These changes did not result in T cell activation in the gut or gut barrier disruption. Strikingly, microbiota depletion in WT mice resulted in decreased heart T cell infiltration, decreased cardiac fibrosis, and protection from systolic dysfunction in response to TAC. Spontaneous reconstitution of the microbiota partially reversed these effects. We observed decreased cardiac expression of the Aryl hydrocarbon receptor (AhR) and enzymes associated with tryptophan metabolism in WT mice, but not in Tcra −/- mice, or in mice depleted of the microbiota. These findings demonstrate that cardiac pressure overload induced gut dysbiosis and T cell immune responses contribute to adverse cardiac remodeling, and identify the potential contribution of tryptophan metabolites and the AhR to protection from adverse cardiac remodeling and systolic dysfunction in HF. Graphical abstract: